2017
DOI: 10.12783/dtetr/icaenm2017/7801
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5, Investor Sentiment, and Stock Returns

Abstract: This paper investigates how PM2.5 affects the stock price of firms from heavy polluting industries and environment-friendly industries in China, applying the emotion cognition theory into the investor sentiment theory framework. We argue that PM2.5 will affect people's emotion, which in turn, affect their investing decision. Meanwhile, people will attribute the release of PM2.5 to heavy polluting firms, when have better predictions for environment-friendly firms. The empirical results are consistent with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It was found that AQI is negatively associated with stock returns, and this relation was stronger when the trader was investing more polluted areas. Taking off from the findings of this study, many studies have emerged from China which is fighting extreme effects of pollution like haze pollution and high levels of PM 2.5 in its cities [13][14]. These studies in China have found that trading volumes were affecting by air quality in short term, thus providing the link between investor mood and stock performance.…”
Section: Literature Surveymentioning
confidence: 72%
“…It was found that AQI is negatively associated with stock returns, and this relation was stronger when the trader was investing more polluted areas. Taking off from the findings of this study, many studies have emerged from China which is fighting extreme effects of pollution like haze pollution and high levels of PM 2.5 in its cities [13][14]. These studies in China have found that trading volumes were affecting by air quality in short term, thus providing the link between investor mood and stock performance.…”
Section: Literature Surveymentioning
confidence: 72%
“…However, for the same market, Hao (2020) found a non-significant relationship. Huang (2017) applied the emotion recognition theory to relate investors' PM2.5-induced emotions to investor sentiment, which eventually led to negative stock returns. Huang (2017) found that for China, the effects were negative for heavily polluting firms.…”
Section: Introductionmentioning
confidence: 99%
“…Huang (2017) applied the emotion recognition theory to relate investors' PM2.5-induced emotions to investor sentiment, which eventually led to negative stock returns. Huang (2017) found that for China, the effects were negative for heavily polluting firms. Environmentally friendly firms exhibited a positive relationship.…”
Section: Introductionmentioning
confidence: 99%